2013
DOI: 10.1583/13-4242.1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of 5358 Patients Undergoing Direct Open Bypass or Endovascular Treatment for Aortoiliac Occlusive Disease: A Systematic Review and Meta-Analysis

Abstract: Although this study was limited by a paucity of randomized control trials, these results demonstrate superior durability for open bypass, although with longer LOS and increased risk for complications and mortality, when compared to the endovascular approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
0
17

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(131 citation statements)
references
References 61 publications
5
109
0
17
Order By: Relevance
“…Mortality for open aortobifemoral bypass has been estimated to be around 2.6%. 4 A large single center study of 822 patients reported an even lower mortality of 0.1%. 27 To date no randomized controlled trial has shown a difference in mortality between the two techniques.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Mortality for open aortobifemoral bypass has been estimated to be around 2.6%. 4 A large single center study of 822 patients reported an even lower mortality of 0.1%. 27 To date no randomized controlled trial has shown a difference in mortality between the two techniques.…”
Section: Discussionmentioning
confidence: 98%
“…Notwithstanding a marked improvement in safety in the last decades, open AIOD surgery is still associated with a high level of morbidity and mortality. 3,4 Inspired by the successes of minimally invasive laparoscopic procedures in abdominal surgery, Dion and colleagues 5,6 performed the first laparoscopically assisted aortobifemoral bypass in 1993 and the first totally laparoscopic procedure in 1995. Laparoscopic aortobifemoral bypass has been performed at the authors' center since 2003.…”
Section: Introductionmentioning
confidence: 99%
“…The absent femoral pulses on clinical examination clinched the diagnosis of vascular origin of paraplegia in this case. Urgent CT-aortogram confirmed the diagnosis and helped in decision making for appropriate management [8]. Management strategies for such patients include anticoagulants, thrombolysis, embolectomy, endovascular techniques and extra-anatomical bypass with varying degrees of success [9].…”
Section: Discussionmentioning
confidence: 99%
“…The last measured HbA1c was 8.0%, approximately six years prior to presentation. We suspect that the resolution of his infections, combined with regular endocrinology follow-up, contributed to the drastic decrease in HbA1c [52,53].…”
Section: Glycosylated Hemoglobinmentioning
confidence: 99%